Distribusi Frekuensi Kejadian Postpartum Blues Pada Ibu Pascamelahirkan - Nabilah Tarisa; Fonda Octarianingsih; Festy Ladyani; Woro Pramesti (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Postpartum depression in postpartum mothers usually begins with the postpartum blues or baby blues or maternity blues. This type of research is a quantitative descriptive using a demographic data questionnaire and the EPDS (Edinburgh Postpartum Depression Scale) questionnaire as primary data. The sample used a total sampling technique with a sample size of 40 respondents. Data analysis is used to determine the frequency distribution and see the relationship between characteristics. In this study, it was found that in 40 postpartum mothers, 7 respondents (17.5%) were detected as having postpartum blues, and 33 respondents (82.5%) were not affected by Postpartum blues. Whereas there is a relationship between the postpartum blues and the characteristics of respondents based on age and income and age of income